Adolescent Verbal Violent Behavior and Emotional Intelligence: A Cross-Sectional Study - Yunita, Rizka; Isnawati, Iin Aini (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
In today's world, verbal violence is a prevalent issue, especially among adolescents. Typically, the perpetrators are the victims' peers, and this can have detrimental effects on the victims, including a decrease in emotional intelligence. The purpose of the study was to examine the relationship between peer verbal violence and emotional intelligence in adolescents. The study utilized a cross-sectional design and involved 120 teenage boarding school students, with a sample of 92 active adolescent students selected through simple random sampling. The research instruments included a bullying questionnaire (consisting of 12 questions) adapted from Tower and an emotional intelligence self-assessment tool (comprising 20 questions) adapted from Sterret. Data analysis was conducted using the Spearman Rank Test, which revealed a significant relationship (ρ value of 0.000) between peer verbal violence and emotional intelligence in adolescents. The study highlighted the adverse effects of peer verbal violent behaviour, such as hindering self-development, reducing empathy, and causing anxiety and shame, as well as potentially triggering similar violent behaviour by the perpetrator. As a result, it emphasizes the need for schools to take collaborative action to minimize violent verbal behaviour.